Mitigation of the Fasād Al-Niyyah Against Scientific Morality in the Framework of Modern Islamic Education - Azmi, Diinu Tsabit; Achmad, Mukhsin (Tawazun: Jurnal Pendidikan Islam, 2026)
Modern Islamic education is faced with a complex situation. On one hand, Islamic educational institutions hold a strategic role in character building; on the other hand, educational practices are often trapped in academic formalities that fail to stem moral degradation and the ecological crisis. This condition is exacerbated by the phenomenon of fasād al-niyyah (corruption of intention), where the orientation of scientific development shifts from public welfare to the mere pursuit of profit and personal ambition. This study aims to elaborate on the role of scientific morality within the framework of Islamic education as a mitigation instrument to address moral and environmental crises. Using a qualitative method through library research, this study analyzes the relationship between scientific logic (Manṭiq) and the objectives of Sharia (Maqāṣid al-Syarī‘ah). The results indicate that the current ecological crisis stems from the separation of intellectual intelligence and moral responsibility. This research proposes integrating the Manṭiq tradition, which views science not merely as a cognitive tool, but as an organic unity between ṣiḥḥat al-fikr (logical correctness), ṣidq al-ma‘nā (truth of reality), and ṣalāḥ al-athar (moral benefit). The novelty of this research lies in the repositioning of fasād al-niyyah as a key variable for diagnosing the failures of modern research, offering a science education framework where morality perfects logic, and logic strengthens scientific morality to maintain ecological balance in accordance with the principles of Maqāṣid al-Syarī‘ah. Abstrak Pendidikan Islam modern dihadapkan pada situasi yang kompleks. Di satu sisi, institusi pendidikan Islam memiliki peran strategis dalam pembentukan karakter, di sisi lain, praktik pendidikan sering terjebak pada formalitas akademik yang gagal membendung degradasi moral hingga krisis ekologi. Kondisi ini diperparah oleh fenomena fasād al-niyyah (kerusakan niat), di mana orientasi pengembangan ilmu pengetahuan bergeser dari kemaslahatan publik menjadi sekadar pengejaran profit dan ambisi pribadi. Penelitian ini bertujuan untuk menguraikan peran moralitas keilmuan dalam bingkai pendidikan Islam sebagai instrumen mitigasi untuk mengatasi krisis moral dan lingkungan. Penelitian ini menggunakan metode kualitatif melalui studi pustaka dengan menganalisis hubungan antara logika keilmuan (Manṭiq) dan tujuan syariat (Maqāṣid al-Syarī‘ah). Hasil penelitian menunjukkan krisis ekologi saat ini berpangkal pada pemisahan antara kecerdasan intelektual dan tanggung jawab moral. Mengintegrasikan tradisi Manṭiq yang memandang ilmu bukan sekadar alat kognitif, melainkan kesatuan organik antara ṣiḥḥat al-fikr (ketepatan logika), ṣidq al-ma‘nā (kebenaran realitas), dan ṣalāḥ al-athar (kemanfaatan moral). Kebaruan penelitian ini terletak pada reposisi fasād al-niyyah sebagai variabel kunci untuk mendiagnosis kegagalan riset modern, menawarkan kerangka pendidikan sains dimana moralitas menyempurnakan logika, dan logika menguatkan moralitas ilmu demi menjaga keseimbangan alam sesuai prinsip Maqāṣid al-Syarī‘ah.